The Blues brothers [videorecording (DVD)] - Belushi, John; Aykroyd, Dan; Landis, John, 1950- (Universal, 2005)
After Jake Blues is release from prison, he and brother Elwood go to visit the old home where they were raised by nuns. They learn the church is no longer supporting the institution and will sell the place to the education authority. The only way to keep the place open is if the